APPLICATION OF VIRTUAL REALITY DISTRACTION THERAPY TO PAIN LEVELS IN AH CHILDREN WITH TONSILLECTOMY POST SURGERY AT GRAHA HERMINE HOSPITAL BATAM CITY - Pramadhani, Wulan; Riswan, L.D (Journal of Nursing Periodic, 2025)
Introduction: Post tonsillectomy surgery, patients usually experience significant throat pain, difficulty swallowing, and possibly a low-grade fever. The recovery period generally takes about 7 to 14 days. Pain is an unpleasant emotional as well as sensory experience associated with the possibility or presence of tissue injury. When providing services to children, the primary goal is to take steps to reduce the pain and stress that accompanies the medical treatment that children have to undergo. The main aim of the service is to provide children with atraumatic, or non- traumatic care. Methods: The purpose of the study was to explain nursing care related to the provision of distraction interventions using virtual reality in pain management in patients with postoperative tonsillectomy. The research was conducted in the Pediatric Treatment Room, Graha Hermine Hospital, Batam City. Results: Patients diagnosed with tonsil hypertrophy post tonsillectomy surgery were given distraction therapy interventions using virtual reality for 3 days and in a day it was carried out 2 times, namely at noon and in the afternoon. Patients can choose the video they want to watch during the 15-20 minute therapy session. Deep breathing exercises and pharmaceutical therapy were also included. Conclusions: From the results of the study, it can be said that if the provision of distraction therapy nursing interventions using virtual reality has an effect on reducing pain intensity, along with the vital signs of postoperative tonsillectomy patients.